Blueprint for an Agricultural Recovery Plan for Ukraine - Broyaka, Antonina; Dankevych, Vitalii; Dodd, Emma; Welsh, Caitlin (Center for Strategic and International Studies, 2025)
Russia’s full-scale invasion of Ukraine in February 2022 significantly disrupted Ukraine’s agriculture sector, which is a pillar of its national economy and a key player in global food trade. It could take years or even decades for Ukraine’s farmland, agricultural infrastructure, logistics routes, agricultural labor force, and agribusiness environment to recover from the destruction suffered throughout the war. This report aims to provide the government of Ukraine and its partners with a sequenced road map for Ukraine’s agricultural recovery that positions the sector for a sustainable and economically competitive future.
Keywords: Ukraine; agriculture; recovery; foreign investment; food security; international development